TELAAH FILOSOFIS TERHADAP UNDANG-UNDANG PERKAWINAN NOMOR 1 TAHUN 1974 PASAL 7 AYAT (1) TENTANG BATAS USIA PERNIKAHAN - N, Nastangin (Ahkam: Jurnal Hukum Islam, 2020)
Underage marriage is marriage between men and women who both have not reached the age of 19 years for men and 16 years for women according to the regulations in the Marriage Law No. 1 of 1974. Marriage is done legally in formal lawand state law. State that is invalid if it does not meet the requirements. In the perspective of religion, underage marriage is marriage carried out by people who have not been mature. The majority of Islamic Law experts legalize early marriage. This understanding is the result of the interpretation of Q.S.Ath-Thalak: 4 and historical records The Prophet married Aisyah at a young age. Some scholars also legalize underage marriage has become a consensus of Islamic law experts. The purpose of this paper is to find out the nature of the existence of marriage records. This research uses a philosophical approach, by explaining the nature and wisdom of its formal object. The conclusion is that there is age limitation to give benefit to someone who wants to get married because age is very influential on family life